RHYTHM DISTURBANCES DURING COLONOSCOPY - D. Jordanov; Ivailo P. Vazharov (Peytchinski Publishing, 2012)
Purpose: The purpose of this study is to assess the risk of inducing rhythm disturbances of the heart during colonoscopy.Patients and methods used: 80 patients had undergone colonoscopyper formed by two experienced specialists of endoscopy for the period from March to December 2011. The endoscopies were performed without premedication and sedation. Holter was placed on each patient one hour before the endoscopic examination, and the record continued one hour after the manipulation. The blood pressure was measured before, during and after the procedure.Results: During colonoscopy 25 patients (31,25%) manifested rhythm disorders. In 15 patients (18,75%) sinus tachycardia occurred. In 7 patients (8,75% ) suptraventricular extra systoles were observed and in 3 patients (3,75%) - ventricular extra systoles. No ST-T changes were found. Highest values of the blood pressure were measured before and during the endoscopy, but the values did not exceed 160/105 mmHg. In 10 patients (12,5%) a hypotensive reaction was observed, bur the values were not lower than 80/ 50. In 2 patients there was a short bradycardia with a heart frequency 50-55 /min.Conclusions: Our results showed that the rhythm disorders during lower colonoscopy occur in approximately 1/3 of the examined patients, there is an increase or decrease of the blood pressure in some patients, but that doesn't require physician's aid and the examination can be carried out safely without monitoring.